'Comparative Reprehensibility' and the Fourth Amendment Exclusionary Rule - Kamisar, Yale (1987)
It is not . . . easy to see what the shock-the-conscience test adds, or should be allowed to add, to the deterrent function of exclusionary rules. Where no deterrence of unconstitutional police behavior is possible, a decision to exclude probative evidence with the result that a criminal goes free to prey upon the public should shock the judicial conscience even more than admitting the evidence. So spoke Judge Robert H. Bork, concurring in a ruling that the fourth amendment exclusionary rule does not apply to foreign searches conducted exclusively by foreign officials. A short time thereafter, when an interviewer read back the above statement and invited him to comment further on the subject, Judge Bork responded: [One of the reasons] sometimes given [in support of the exclusionary rule] is that courts shouldn't soil their hands by allowing in unconstitutionally acquired evidence. I have never been convinced by that argument because it seems the conscience of the court ought to be at least equally shaken by the idea of turning a criminal loose upon society. Judge Bork displays no affection for the exclusionary rule, but he may not be making an affirmative case against it. All he may be saying is that whatever good reasons may exist for excluding illegally seized evidence, the judges shouldn't soil their hands argument isn't one of them. On the other hand, Bork may be implying something more - or at least a reader may understandably infer something more: Where the defendant's conduct is more reprehensible than the police officer's (as, of course, it usually will be), the judges shouldn't soil their hands argument is a good reason for admitting illegally seized evidence. For judges soil their hands a good deal more by turning a criminal loose upon society than they do by simply ignoring an officer's violation of the fourth amendment. To put it somewhat differently, if the admissibility of illegally seized evidence turns solely on how the ruling affects the judge's conscience, the defendant's motion to suppress should almost always fail. For a judge ought to lose a lot less sleep over admitting highly probative, albeit tainted, evidence than she should over freeing an apparently guilty person to prey upon society again